ANALISIS PENGARUH KEUANGAN DIGITAL TERHADAP PERTUMBUHAN EKONOMI ISLAM - Riska Febrian; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
In an increasingly digital era, digital finance is a solution to encourage Islamic economic growth. The integration of digital finance in the Islamic economy offers great opportunities to strengthen and expand the Islamic financial system. This research aims to analyze how digital finance contributes to Islamic economic growth and the future prospects of digital finance in supporting Islamic economic growth. The method used in this research is a library research methodology. The research results show that digital finance contributes significantly to Islamic economic growth through financial inclusion, transaction efficiency, product innovation and transparency. Digital finance has very promising prospects in supporting Islamic economic growth. Digital finance can play a key role in promoting economic growth that is more inclusive, efficient and comparable to sharia principle.